Carotid Body Ablation Abrogates Hypertension and Autonomic Alterations Induced by Intermittent Hypoxia in Rats. Issue 2 (August 2016) - Del Rio, Rodrigo; Andrade, David C.; Lucero, Claudia; Arias, Paulina; Iturriaga, Rodrigo
Abstract : Chronic intermittent hypoxia (CIH), the main feature of obstructive sleep apnea, enhances carotid body (CB) chemosensory responses to hypoxia and produces autonomic dysfunction, cardiac arrhythmias, and hypertension. We tested whether autonomic alterations, arrhythmogenesis, and the progression of hypertension induced by CIH depend on the enhanced CB chemosensory drive, by ablation of the CB chemoreceptors. Male Sprague–Dawley rats were exposed to control (Sham) conditions for 7 days and then to CIH (5% O2, 12/h 8 h/d) for a total of 28 days. At 21 days of CIH exposure, rats underwent bilateral CB ablation and then exposed to CIH for 7 additional days. Arterial blood pressure and ventilatory chemoreflex response to hypoxia were measured in conscious rats. In addition, cardiac autonomic imbalance, cardiac baroreflex gain, and arrhythmia score were assessed during the length of the experiments. In separate experimental series, we measured extracellular matrix remodeling content in cardiac atrial tissue and systemic oxidative stress. CIH induced hypertension, enhanced ventilatory response to hypoxia, induced autonomic imbalance toward sympathetic preponderance, reduced baroreflex gain, and increased arrhythmias and atrial fibrosis. CB ablation normalized blood pressure, reduced ventilatory response to hypoxia, and restored cardiac autonomic and baroreflex function. In addition, CB ablation reduced the number of arrhythmias, but not extracellular matrix remodeling or systemic oxidative stress, suggesting that reductions in arrhythmia incidence during CIH were related to normalization of cardiac autonomic balance. Present results show that autonomic alterations induced by CIH are critically dependent on the CB and support a main role for the CB in the CIH-induced hypertension. Abstract : Supplemental Digital Content is available in the text.